2017
DOI: 10.11648/j.ajn.20170301.11
|View full text |Cite
|
Sign up to set email alerts
|

Improving the CO Sensing Properties of Ferrocene Modified Polypyrrole/Silicon Carbide Nanocomposite Films Synthesized by Electrochemical Deposition

Abstract: Abstract:In this study, SiC nanoparticles 40 nm in diameter were added to ferrocene-modified conducting polymer (FcPPy) films to improve the signal/noise ratio of a sensor. The increased porosity of the Fc-PPy/SiC nanocomposite film produces a larger active surface area with more active sites available for adsorption. Electrochemical deposition was used to fabricate nanocomposite films (PPy, Fc-PPy, PPy/SiC and Fc-PPy/SiC), on both QCM and interdigitated electrodes, to measure CO concentration. All nanocomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Few studies have reported the comparison between IDE versus QCM technologies for the detection of various analytes in gas, vapor, or solution phases. From this work, some general trends can be surmised. Both devices seem to show similarities in terms of sensitivity, response/recovery times, repeatability, or long-term stability.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported the comparison between IDE versus QCM technologies for the detection of various analytes in gas, vapor, or solution phases. From this work, some general trends can be surmised. Both devices seem to show similarities in terms of sensitivity, response/recovery times, repeatability, or long-term stability.…”
Section: Discussionmentioning
confidence: 99%